MODERASI BERAGAMA UNTUK PERSATUAN DAN KESATUAN BANGSA INDONESIA - Salsabila Azahra; Zaenul Slam (Jurnal Riset Sosial Humaniora dan Pendidikan, 2022)
This research has the aim of knowing and studying religious moderation for the unity and integrity of the Indonesian state. This research uses a qualitative approach by describing the importance of religious moderation to maintain the unity and oneness of the Indonesian nation. This study uses the library study method where the results obtained will be described. From this study it was found that religious moderation in maintaining the unity and integrity of the Indonesian nation has a fairly important role. From the results of this study it was also found that forms of religious moderation to maintain the unity and integrity of the Indonesian nation can be implemented in everyday life including bringing an attitude of tolerance to each individual, holding deliberations to achieve common goals, having tolerance, having different thoughts. innovative and dynamic.